2013
DOI: 10.1248/bpb.b212020
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Pharmacological Properties of the Pulmonary Vein Myocardium

Abstract: The pulmonary vein contains a myocardial layer extending from the left atrium, which is receiving attention as the source of ectopic electrical activity underlying atrial fibrillation. Electrophysiological and pharmacological analysis of the pulmonary vein myocardium performed in various experimental animal species have revealed characteristics such as presence of intracellular Ca 2+ oscillations and low repolarizing potency. The automaticity of the pulmonary vein myocardium is affected by various neurotransmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…On the other hand, several reports, including those from our laboratory, showed that the automaticity of the pulmonary vein myocardium is dependent on intracellular calcium ion. 4,5) In the guinea pig pulmonary vein myocardium, constant electrical firing was enhanced by interventions which increase intracellular calcium ion such as repetitive electrical stimulation 16) and ouabain treatment. 6) Thus, another probable mechanism for the enhancement of automaticity by mechanical stretch is the increase in supply of calcium ion to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several reports, including those from our laboratory, showed that the automaticity of the pulmonary vein myocardium is dependent on intracellular calcium ion. 4,5) In the guinea pig pulmonary vein myocardium, constant electrical firing was enhanced by interventions which increase intracellular calcium ion such as repetitive electrical stimulation 16) and ouabain treatment. 6) Thus, another probable mechanism for the enhancement of automaticity by mechanical stretch is the increase in supply of calcium ion to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The blood pressure of the pulmonary circulation as well as the level of autonomic and hormonal influence are known to be altered under various pathological conditions. 4,5,13) Whether blockers of SACs are effective against various models of atrial fibrillation is a matter of great interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, it is clear that when PVCs do generate APs they can prevent atrial myocytes from faithfully following the physiological pacemaking signals emanating from the SA node. For this reason, PVCs are a clinically-recognized source of pro-arrhythmic signals in the heart [15]. Ablation procedures are routinely used by clinicians to electrically isolate pulmonary veins from the posterior wall of the left atrium (the border of the two tissues) and they are highly successful in treating acute and sustained AF [16,17].…”
Section: Pulmonary Vein Sleeve Cells Show Spontaneous Action Potentiamentioning
confidence: 99%
“…Procedures that prevent the electrical continuity between PVCs and atrial myocytes are highly effective in treating AF, but can have serious side effects [28]. Although it is known that PVCs are a trigger of arrhythmic activity, exactly how these cells generate arrhythmic signals are less clear [15]. We and others, have hypothesized that spurious Ca 2 + signals are a potent source of arrhythmic activity [23,29,30].…”
Section: Individual Pulmonary Vein Sleeve Cells Differ In Their Pattementioning
confidence: 99%